1987
DOI: 10.7326/0003-4819-106-6-793
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Treadmill Score for Predicting Prognosis in Coronary Artery Disease

Abstract: To determine the prognostic value of the treadmill exercise test, we evaluated 2842 consecutive patients with chest pain who had both treadmill testing cardiac catheterization. The population was randomly divided into two equal-sized groups and the Cox regression model was used in one to form a treadmill score that was then validated in the other group. The final treadmill score was calculated as follows: exercise time--(5 X ST deviation)--(4 X treadmill angina index). Using this treadmill score, 13% of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
304
1
32

Year Published

1994
1994
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 587 publications
(343 citation statements)
references
References 22 publications
6
304
1
32
Order By: Relevance
“…2,3,11 However, the shortcomings of ST-segment analysis may reflect the limitations of using a single cutoff of ST-segment depression, and this may be addressed by assessment of ST segment as a continuous variable, for example using the ST/heart-rate slope 12 or a multivariate score such as the Duke treadmill score. 13,14 Myocardial perfusion imaging may also present inaccuracies because of false-positive and negative results caused by disturbed coronary flow reserve, partial volume issues, and reduced exercise capacity, 15,16 although there are reports of more favorable accuracy. 17 The definitive study for the comparison of stress echocardiography with single-photon emission computed tomography (SPECT) was reported by Fragasso, 1 who compared dobutamine stress echocardiography with dipyridamole stress 99 mTc-MIBI stress/rest myo- Figure 3.…”
Section: Assessment Of Cad In Patients With Hypertension and LV Hypermentioning
confidence: 99%
“…2,3,11 However, the shortcomings of ST-segment analysis may reflect the limitations of using a single cutoff of ST-segment depression, and this may be addressed by assessment of ST segment as a continuous variable, for example using the ST/heart-rate slope 12 or a multivariate score such as the Duke treadmill score. 13,14 Myocardial perfusion imaging may also present inaccuracies because of false-positive and negative results caused by disturbed coronary flow reserve, partial volume issues, and reduced exercise capacity, 15,16 although there are reports of more favorable accuracy. 17 The definitive study for the comparison of stress echocardiography with single-photon emission computed tomography (SPECT) was reported by Fragasso, 1 who compared dobutamine stress echocardiography with dipyridamole stress 99 mTc-MIBI stress/rest myo- Figure 3.…”
Section: Assessment Of Cad In Patients With Hypertension and LV Hypermentioning
confidence: 99%
“…All patients underwent infusion of dipyridamole (0.56 mg/kg over 4 minutes), followed immediately by symptom-limited treadmill exercise with a standard Bruce protocol and usual end points. Exercise capacity, symptom status, and ECG changes with stress were noted in all patients and were used to calculate the Duke treadmill score, as previously described 11 : Patients with scores above ϩ5 and below Ϫ10 were considered as being at low and high risk, respectively.…”
Section: Exercise-dipyridamole Stressmentioning
confidence: 99%
“…[3][4][5] The guidelines acknowledge that the elderly and women represent special populations in whom treadmill testing may be less accurate, but there are insufficient data to recommend stress imaging over standard treadmill testing in these groups. We recently reported that the Duke treadmill score 6,7 failed to stratify elderly patients according to risk. 8 Although single-photon emission computed tomography (SPECT) generally is more accurate for prognostic purposes than standard treadmill testing, 9 -13 there are few published data on the prognostic value of exercise myocardial perfusion imaging in the elderly, especially elderly women.…”
mentioning
confidence: 99%